The Effect of the Covid-19 Pandemic on Sharia Monetary Transmission in Indonesia - Lavlimatria Esya; Deden Misbahudin Muayyad (Unisia, 2021)
This research analyzed the effect of the COVID-19 pandemic on sharia monetary transmission in Indonesia through channel financing on money supply (M2). It was conducted to determine the stationary, cointegration, and optimal lag using Vector Error Regression Model (VECM), Granger Causality Test, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). Secondary data were collected from the monthly variables M2, SBIS, PUAS, Islamic Banking Financing, and the COVID-19 pandemic (Dummy Variable) from January 2010 to December 2020. Furthermore, VECM model showed that in the long term, sharia monetary instrument variables, such as SBIS and PUAS, are significant and positive in affecting M2, while Financing (FIN) and the COVID-19 pandemic are insignificant. This also shows that in the short term, only PUAS is significant.